PENGARUH PENGGUNAAN MEDIA NOVEL GRAFIS DIGITAL KERAJAAN PONTIANAK PADA PEMBELAJARAN SEJARAH TERHADAP KESADARAN BUDAYA DI SMK NEGERI PONTIANAK - Astrini Eka Putri; Haris Firmansyah (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2022)
The Influence of The Use of Digital Graphic Novel Media Of Pontianak Kingdom on Historical Learning On Student Cultural Awareness in SmK Negeri Pontianak. Tradition becomes a major pointer in the content of learning history today. Character education that is the focus of national education today, in line with the goal of historical learning in general is to educate noble characters through history. The research uses quantitative methods with experimental quasi research designs. Based on the results of research obtained from statistical tests on cultural awareness questionnaires, it can be stated that there are differences in influences on student cultural awareness attitudes between X TKJ and X Ak. This is known from sig 0.002 < 0.05. It can then be stated that there is a significant difference in student cultural awareness between X TKJ and X Ak. Therefore, it can be concluded that there is an influence on the application of digital graphic novel media based on the Kingdom of Pontianak on historical learning to cultural awareness in Pontianak State Vocational School.